Emotional cues and concerns of patients with a life limiting, chronic illness during advance care planning conversations in general practice. (February 2023) - De Vleminck, Aline; Craenen, Lara; Stevens, Julie; Lemaigre, Valentine; Pype, Peter; Deliens, Luc; Pardon, Koen
Abstract: Objective: To explore a) to what extent patients with serious illness express emotional cues and concerns during advance care planning (ACP) conversations with their general practitioner (GP), b) the content of cues/concerns and c) GPs' responses to cues/concerns. Methods: Cues/concerns and GPs' responses in 20 conversations were coded using the Verona Codes (VR-CoDES and Verona Codes-P). A qualitative thematic analysis was used to identify overarching themes within the content of the cues/concerns. Results: A total of 216 cues/concerns were identified (range: 1–28; mean: 13) in 85% of conversations; with 85% of these being cues/implicit expressions of emotions. In 72% of responses, the GP provided space for the patient to elaborate on cues/concerns. The most common theme cues/concerns were expressed about was "the consequences of illness on quality of life and burdening others". Conclusion: Emotions were mainly communicated implicitly as cues and the content varied greatly. The amount of cues/concerns expressed show that ACP can evoke many emotions. Practice implications: GPs should be attentive to implicit expressions of emotions as these provide opportunities to engage patients in tailored ACP conversations. As patients expressed many cues/concerns, GPs are recommended to have recurrent conversations with patients and actively ask about diverse ACP topics. Highlights: Patients expressed many cues/concerns during advance care planning conversations. The content of the cues/concerns varied greatly. Most cues/concerns were expressed about patients' values and quality of life. GPs responded more often with space providing than space reducing responses.